Preliminary screening and microbiological evaluation on the environmental hygiene for galley equipment, safety equipment and cabin common facilities of a local airline in Malaysia - Wing, G.K.; Rollon, D.W.; Kuan, C.H.; Ajau, D.; M.A.R., Nor-Khaizura; Hasan, H.; Radu, Son (Rynnye Lyan Resources, 2022)
Over the last two decades, only a handful of research have been conducted pertaining to food safety in the aviation industry. The gap of knowledge in in-flight food safety literature has long been silenced. Therefore, it was the objective of this study to conduct preliminary screenings to evaluate the environmental quality of the service equipment (GE), safety equipment (SE) and common facilities (CF) within the confinement of commercial aeroplanes in Malaysia. A total of 112 swab samples (n = 112) were analyzed to detect the prevalence of Escherichia coli, Vibrio, Salmonella and coliforms using conventional microbiological methods. The qualitative aerobic mesophilic plate count revealed that 99 (88.39%) and 13 (11.61%) were reported as positive and negative samples, respectively. It was reported that all 17 samples taken from the long-haul flight were positive, with 8 (9.14%), 4 (3.57%) and 5 (4.46%) samples belonging to the GE, SE, and CF, respectively. Forty-five positive swab samples taken from medium-haul flight sectors showed that 30 (26.79%), 8 (9.14%), 7 (6.25%) samples were that of the GE, SE, and CF, respectively. Meanwhile, 19 (16.96%), 8 (9.14%), and 10 (8.93%) of the shorthaul flights samples were that of the GE, SE, and CF, respectively. It was therefore concluded that GE, SE and CF were reported at 57 (50.89%), 20 (17.86%) and 22 (19.64%), respectively. In view of the large numbers and high percentages of positive sample results, it is our opinion that the cleaning, sanitizing and disinfecting procedures of the galley equipment, safety equipment and common facilities are revisited. The assurance in conformance to the hazard analysis and critical control points (HACCP) management system may enhance the safety and reliability of all stakeholders especially the flight attendants who are the final custodians of the environmental hygiene and that of themselves.